Synthesis and Characterization of K2O/ACT Catalyst for Biodiesel Production from Beef Fat Waste - Putri, Vani Dwi Hani; Samik, Samik (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The increasing use of petroleum as fuel has depleted fuel, so alternative fuels such as biodiesel are needed because they are environmentally friendly and come from vegetable and animal sources. Therefore, this article presents biodiesel production from beef fat using a K2O/ACT heterogeneous base catalyst derived from egg shells. The Eggshell becomes a CaO catalyst after 3 hours of calcination at 900°C. The K2O/ACT catalyst was synthesized by impregnating CaO with KOH and characterized using XRD and BET. The K2O/ACT catalyst was compared to the CaO catalyst for transesterification activity under appropriate conditions (reaction temperature 65°C, catalyst loading 3% by weight, oil to methanol molar ratio 1:12, and reaction time 3 hours). The catalytic activity of the catalyst was determined to be 98.40% Fatty Acid Methyl Ester (FAME). The insertion of K2O into the CaO catalyst increases the basicity characteristics, thereby increasing the catalytic activity of transesterification.